Danish Students’ Interactions With PIRLS Items - Marie-Louise Molbæk; Rebekka Hegaard Gabrielson; Katja Neubert; Simon Skov Fougt (Nordic Journal of Literacy Research)
This article is based on a qualitative research project related to PIRLS (Progress in International Reading Literacy Study). We explore how 25 Danish students from two fourth-grade classes interact with PIRLS items as readers and writers. We focus on two specific constructed-response items from a literary text used in PIRLS 2016 by examining and comparing students’ written responses to these items and oral responses expressed during interviews. To some extent, students’ text interactions differ from expectations presented in the international scoring guide. Based on our analysis, which draws on reader-response theory, we find that the scoring guide largely expects students to assume an efferent or discursive approach to reading, whereas many students in this study seem to approach texts and respond to items based on a more personal literary experience. We also find that the written student responses contain less elaboration than their oral responses. In this article, we discuss both written and oral responses as indicators of reading comprehension in PIRLS and the inferences related to student performance, with a focus on aesthetic and efferent reading.